Neo Boys. - Sander, Daniel (Pivot: Journal of Interdisciplinary Studies & Thought, 2016)
This paper considers William S. Burroughs's nonfictional long-form essay The Electronic Revolution (1970) and contemporaneous fictional novel The Wild Boys: A Book of the Dead (1971) alongside some moments from the early work of Patti Smith, including her time with the Patti Smith Group and their four albums together between 1975 and 1979. I align Burroughs's concepts of the word virus and wild boy - concepts subsequently taken up by Smith - with the three luxuries of nature identified by intellectual Georges Bataille in his theorization of general, or solar, economy. The parasitic and proliferative appearance of Burroughs's writing and Smith's performances - artworks that resemble electronic spam and speaking in tongues - bear some resemblance to the alien duplicates in Invasion of the Body Snatchers insofar as these artists waste their textual and physical bodies from within, thereby working against the sociolinguistic logic of identity.